A Co-culture Model of PBMC and Stem Cell Derived Human Nasal Epithelium Reveals Rapid Activation of NK and Innate T Cells Upon Influenza A Virus Infection of the Nasal Epithelium - Luukkainen, Annika; Puan, Kia Joo; Yusof, Nurhashikin; Lee, Bernett; Tan, Kai Sen; Liu, Jing; Yan, Yan; Toppila-Salmi, Sanna; Renkonen, Risto; Chow, Vincent T.; Rotzschke, Olaf; Wang, De Yun (Frontiers in Immunology, 2018)
Background: We established an in vitro co-culture model involving H3N2-infection of human nasal epithelium with peripheral blood mononuclear cells (PBMC) to investigate their cross-talk during early H3N2 infection. Methods: Nasal epithelium was differentiated from human nasal epithelial stem/progenitor cells and cultured wtih fresh human PBMC. PBMC and supernatants were harvested after 24h and 48h of co-culture with H3N2-infected nasal epithelium. We used flow cytometry and Luminex to characterize PBMC subpopulations, their activation and cytokines and chemokines secretion. Results: H3N2 infection of the nasal epithelium associated with significant increase in interferons (IFN-, IFN-, IL-29), pro-inflammatory cytokines (TNF-α, BDNF, IL-3) and viral-associated chemokines (IP-10, MCP-3, I-TAC, MIG), detectable already after 24h. This translates into rapid monocytes, NK-cells and innate T-cells (MAIT and γδ T cells) activation, evident with CD38 and/or CD69+ upregulation. Conclusions: This system may contribute to in vitro mechanistic immunological studies bridging systemic models and possibly enable the development of targeted immunomodulatory therapies.